Revealing genetic diversity of wild Phalaenopsis orchids in Thailand through Random Amplified Polymorphic DNA markers - SUREEPORN KATE-NGAM; CHATCHAWAN JANTASURIYARAT; PATCHAREE LAKOTE; THIN PROMCHOT; CHANTAMART CHUEAKAEW (Society for Indonesian Biodiversity, 2023)
Abstract. Kate-ngam S, Jantasuriyarat C, Lakote P, Promchot T, Chueakaew C. 2023. Revealing genetic diversity of wild Phalaenopsis orchids in Thailand through Random Amplified Polymorphic DNA markers. Biodiversitas 24: 5409-5417. Wild Phalaenopsis orchids are widely distributed in Thailand, especially along the banks of the Mekong River. The tremendous decrease in the population of these orchids is a matter of concern for maintaining and preventing genetic loss in the natural ecosystem. This study aimed to determine the genetic diversity of 50 wild Phalaenopsis accessions collected from the northeastern of Thailand using random amplified polymorphic DNA (RAPD) markers. The 204 polymorphic bands generated from 27 RAPD primers were employed for fingerprinting these orchid accessions. Dice’s similarity coefficients ranged from 0.43 to 0.98, with an average of 0.65. In general, a dendrogram constructed based on the unweighted pair group method with arithmetic average (UPGMA) grouped these wild Phalaenopsis accessions into two clusters, namely P. pulcherrima and P. ubonensis clusters. The UPGMA clustering pattern and principal component analysis (PCA) corresponded well with their morphological classification and ploidy level. Our results suggest that this wild Phalaenopsis orchid exhibits a moderate level of relatedness. This might be a consequence of habitat destruction and human over-exploitation which limit gene flow and cause genetic drift among populations. The present finding supports the urgent need for a systematic conservation effort of this orchid species in Thailand.